Embracing the Unexpected: Novice English Teacher's Narrative of Challenges and Joy in Teaching Young Learners - Ardila, Istiqamah; Nisa, Thaibatun (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
Teaching English to young learners presents unique challenges, especially for beginning teachers still developing their professional identity. Many new teachers face emotional and instructional difficulties transitioning from theory to real-life classroom practice. This study explores the lived experiences of a new English teacher in her first year of teaching in an elementary school. The study aims to showcase the teacher's lived experiences using a narrative inquiry approach to uncover unexpected challenges and moments of joy, and to understand how these experiences impact her professional identity. A recent graduate assigned to a public school in Balangan Regency participated in the study, answering interview questions and a narrative framework. Data were analyzed using thematic analysis. The findings revealed three interrelated themes: entering the world of young learners, navigating emotional and instructional turmoil, and maturing alongside the learners. Her journey was filled with feelings of loss and frustration, particularly in managing the classroom and managing emotions. However, there were also moments when she made tangible progress and felt proud of herself. This study recommends that teacher education programs integrate emotional preparation and reflective practice into the curriculum. Furthermore, the findings emphasize the importance of institutional mentoring and ongoing professional development for beginning English teachers in elementary schools. These findings contribute to the broader field of English language teaching by deepening understanding of the emotional and professional characteristics of beginning teachers' experiences and guiding teacher preparation and retention practices.